Skindex-29 scores indicate poor quality of life in early stage mycosis fungoides. Issue 2 (May 2020) - Shalabi, Doaa; Kartan, Saritha; O'Donnell, Megan; Zaya, Romsin; Zhan, Tingting; Shi, Wenyin; Alpdogan, Onder; Porcu, Pierluigi; Nikbakht, Neda
Highlights: Patients with early stage (Stage IA-IB) mycosis fungoides (MF) report poor quality of life on Skindex-29 questionnaire. Regardless of the extent of skin involvement or the type of treatment received, early stage MF patients reported comparable scores on Skindex-29. Patients with no active disease scored significantly higher on questions pertaining to anger and fatigue. Early stage MF patients with minimal or no skin involvement can still be significantly impacted by poor quality of life. There is a need to develop quality of life surveys that fully encompass common concerns of MF patients. Abstract: Background: Questionnaire tools are increasingly being used to assess health related quality of life (HRQOL) in mycosis fungoides (MF) patients. However, a thorough understanding of the factors that lead to poor HRQoL in early stage disease and their distribution across patient subgroups is lacking. Objectives: To characterize factors affecting HRQoL as assessed by Skindex-29 in subgroups of patients with early stage MF seen at a multidisciplinary cutaneous lymphoma clinic. Methods: Skindex-29, a multidimensional survey that evaluates HRQoL (emotions, symptoms, function), was distributed to early stage MF patients. Overall and component scores were analyzed in three groups: no evidence of disease (NED), active disease with limited early stage (AD-T1), and active disease with more extensive early stage (AD-T2). Scores were also compared among patients receiving different treatment modalities. Results: 56 patients (9 NED, 36 AD-T1, and 11 AD-T2) were enrolled in the study. Overall Skindex-29 scores and scores for individual dimensions were comparable among the three sub-groups. Similarly, these scores did not significantly differ among treatment groups or after removal of patients with previous staging higher than IB. Analysis of individual questions revealed that NED patients reported higher scores for questions pertaining to anger and fatigue. Conclusions: Early stage MF patients enrolled in this study had high overall Skindex-29 scores. Surprisingly, Skindex-29 scores of NED patients were comparable to those of patients with active disease, T1 and T2, mostly due to anger and fatigue. Even when skin involvement is minimal or absent, MF patients continue to report impaired HRQoL.